69.0k views
1 vote
3[-x+2(2x+1)]=-1 what does x equal

User Ialexander
by
5.5k points

1 Answer

2 votes

3[-x+2(2x+1)]=-1

Multiply the bracket by 2

(2)(2x)(2)(1)

4x+2

3 [-x+4x+2]=-1

3 [3x+2]=-1

Multiply the bracket by 3

(3)(3x)(3)(2)=-1

9x+6=-1

Move +6 to the other side. Sign changes from +6 to -6

9x+6-6=-1-6

9x=-7

Divide by 9 for both sides.

9x/9=-7/9

x=-7/9

Answer: x=-7/9

User Mr Stanev
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.